Amyand’s Hernia in Adults – an Analysis of Recent Literature - Salati, Sajad Ahmad; AlSulaim, Lamees Sulaiman; Elmuttalut, Mohammad Ahmed (Lietuvos chirurgija, 2024)
Amyand’s hernia is a rare disorder characterized by the presence of the vermiform appendix within an inguinal hernia. It is predominantly found in the pediatric age group, and its occurrence in adulthood is rare. Hence, a systematic analysis of twenty-six case reports of Amyand’s hernia published in the peer-reviewed literature in the year 2023 is presented with emphasis on variables including age of the patient, gender, clinical presentation, side of the inguinal hernia, imaging modalities used for evaluation, achievement of preoperative diagnosis or otherwise, classification, appendix management, hernia management, surgical approach, and outcomes.